Serum biomarkers in normal pressure hydrocephalus - Enra Mehmedika-Suljić; Sebija Izetbegović; Nafija Serdarević; Bekir Rovčanin; Nevena Mahmutbegović; Admir Mehičević; Ibrahim Omerhodžić (Medicinski glasnik, 2023)
Aim: To investigate the serum value of brain derived neurotrophic factor (BDNF), proteins S-100, NSE, IL-6 in normal pressure patients (NPH) compared to control (healthy) group and also a possible correlation with radiological findings in NPH patients. Methods: Study patients were included during the period of 2020-2022. All NPH patients met the diagnostic criteria for probability of NPH. Control patients group included patients without known brain disorder, without clinical symptoms of NPH. Blood samples were taken before planned surgery for NPH. BDNF serum concentrations were assessed by a sensitive ELISA kit, and serum concentrations of S-100, NSE and IL-6 were assessed by using ECLIA technology for immunoassay detection. Results: Among 15 patients who were included, seven NPH patients were compared to eight control patients. Non-significant decrease in BDNF serum concentrations, an increase of protein S-100 serum concentrations, a decrease of NSE serum concentrations, as well as an increase of IL-6 serum concentrations in NPH patients compared to healthy controls was found. Strong positive correlation between BNDF and Evans index was observed (p=0.0295). Conclusion: We did not find a significant difference of BDNF, protein S-100, IL-6 and NSE between serum concentration in NPH and healthy patients. More future research is needed to find the role of BDNF in NPH patients.
Keywords: biomarkers; brain-derived neurotrophic factor; serum